Redefining Rational and Revelation into the Islamic Systemology Concept - Muhammad Aiman Awalluddin (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
The way of thinking held by most Muslims has currently shifted from Allah-centered to logical and empiricism. Also, the separation line of Islam from these practices can be seen clearly as the majority of Muslims hold secular thoughts. Hence, the paper aims to redefine the ‘aqlī (rational) and naqlī (revelation) ways of thinking into the Islamic systemology concept. This is a concept that places Allah as an agent of everything and as the head of the system. Additionally, the process of the evolution of Greek philosophy and how it became a phenomenon in the Muslim world is extensively discussed. The application of rational reasoning, which was championed by Aristotle, is slowly degrading Muslims’ faith, as they have begun to verify everything based on logical answers. This article also strengthens the position of Abū Ḥāmid al-Ghazālī and supports the scholar’s arguments on the rejection of Western philosophy by outlining the importance of yaqīn or strong inner faith in acting and making better judgments. The Islamic systemology concepts are very important to make Muslims aware of the balance between ‘aqlī and naqlī, as both are interconnected and complementary. Ignoring naqlī means Muslims put more emphasis on the world or dunyā and less belief in Allah, and as such, they jeopardize the equilibrium of thinking.